2014
DOI: 10.3402/tellusa.v66.25252
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of tracking methods for extreme cyclones in the Arctic basin

Abstract: A B S T R A C T Dramatic climate changes have occurred in recent decades over the Arctic region, and very noticeably in nearsurface warming and reductions in sea ice extent. In a climatological sense, Arctic cyclone behaviour is linked to the distributions of lower troposphere temperature and sea ice, and hence the monitoring of storms can be seen as an important component of the analysis of Arctic climate. The analysis of cyclone behaviour, however, is not without ambiguity, and different cyclone identificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 57 publications
1
59
0
Order By: Relevance
“…To measure trends in maximum cyclone intensity, these studies have largely focussed on minimum mean sea level pressure (MSLP), and studies generally agree that there is a general reduction in this quantity. A recent intercomparison of cyclone tracking methods by Simmonds and Rudeva (2014) concluded that different methods generally agree on which Arctic cyclones are most intense over the ERA-Interim reanalysis period . However, Chang (2014) cautions that differences in the definitions used in cyclone identification algorithms can lead to differing conclusions when investigating the response of strong cyclones to climate change.…”
Section: Introductionmentioning
confidence: 99%
“…To measure trends in maximum cyclone intensity, these studies have largely focussed on minimum mean sea level pressure (MSLP), and studies generally agree that there is a general reduction in this quantity. A recent intercomparison of cyclone tracking methods by Simmonds and Rudeva (2014) concluded that different methods generally agree on which Arctic cyclones are most intense over the ERA-Interim reanalysis period . However, Chang (2014) cautions that differences in the definitions used in cyclone identification algorithms can lead to differing conclusions when investigating the response of strong cyclones to climate change.…”
Section: Introductionmentioning
confidence: 99%
“…The upper tropospheric trough is the TPV originating upstream at Svalbard [ Simmonds and Rudeva , ]. AC12 then absorbed the other surface cyclone and in the mature stage, and the cyclone's structure became equivalent barotropic with the TPV as it traversed the Arctic Ocean: This is indicative of the vertical vortex coupling mechanism proposed by Aizawa et al [] and Simmonds and Rudeva [], which can lead to rapid intensification of Arctic cyclones. However, clarifying this mechanism is beyond the scope of this paper, since we focus on the formation of AC12 prior to the rapid intensification.…”
Section: Large‐scale and Synoptic Fields In Alera2mentioning
confidence: 94%
“…Recently, Crawford and Serreze () indicated that the baroclinicity affected only on an intensification of ACs. The coupling with lower and upper cyclones was also important for the development of ACs (Simmonds and Rudeva, , ).…”
Section: Introductionmentioning
confidence: 99%